Firewalls fend off invasions from the Net. - Lodin, S.W.
Whether a computer is in a corporation, government agency, university, small business, or at home, if it is linked to a network, hackers are a risk. The first line of defense against them is a firewall, provided it is set up correctly. Firewall technology is a set of mechanisms that collectively enforce a security policy on communication traffic entering or leaving a guarded network domain. The security policy is the overall plan for protecting the domain. Embodied in hardware, software, or both, a firewall guards and isolates the domain. Broadly, firewalls attempt to maintain privacy and ensure the authenticity of data communications that pass through their domain's boundaries. Whether data is entering or leaving a domain, it is protected from eavesdropping (passive wiretapping) and change (active wiretapping). But only communication traffic entering or leaving a domain comes under the influence of firewall technology
Keywords: Internet; Active wiretapping protection; Communication traffic; Computer network; Data communication authenticity; Domain protection; Eavesdropping protection; Firewall technology; Guarded network domain; Passive wiretapping protection; Security policy